Effects of cytokinin in enhancing the multiplication of vegetative hylocereus polyrhizus - Ng, Zhe Cheng; Shiekh Mahmud, Siti Hamidah Radiyah; Tan, Suat Hian (Trans Tech Publications Ltd, Switzerland, 2021)
Hylocereus polyrhizus is a climbing vine cactus species that grows in tropical area. Recently, it has attracted the attention of public as it provides numerous benefits to humans in term of health especially for those who prioritize health over mostly anything. The objective of this research was to assess the effects of different type of cytokinins which were 6-Benzylaminopurine (BAP) and Kinetin in different concentration with combination of waste coconut water and sucrose on enhancing the in vitro multiplication of H. polyrhizus. It was found that BAP had higher effect in shoot multiplication than Kinetin as the highest number of shoots was produced at 3.67± 0.67 when supplemented with 3.0 mg/L of BAP whereas for Kinetin, it only produced 1.75±0.38 shoots and without cytokinin was 1.17±0.01. However, Kinetin had a slightly better effect in shoot elongation than BAP as Kinetin produced shoots with longer length than BAP. It was found that the longest length produced by Kinetin was 2.51±0.06 while BAP was 2.43±0.05 cm and without cytokinin was 2.18±.0.01.For the production of roots, low concentration of cytokinin in range 0.3 mg/L to 1.0 mg/L provides the best number of roots. In conclusion, addition of cytokinin has significant effect in enhancing the growth and multiplication of vegetative H. polyrhizus.